'I feel pretty': beauty as an affective-material process. (April 2022) - Ingram, Toni
This article explores the potential of feminist new materialisms and theories of affect for reframing how we might think about beauty and the body. Through an exploration of girls, beauty and the school ball (prom), the article engages with Karen Barad's concept of intra-action to conceptualise beauty as an affective-material process. This perspective involves an ontological shift in how girls, bodies and beauty are understood; from thinking about beauty and the human as discursively produced, towards a relational approach that conceptualises materiality and affect as co-constitutive forces. The article is interested in how such a framing might invite ways of understanding beauty that avoid binary frameworks, such as good/bad, subject/object and discourse/matter. I consider the potential this might offer feminist analyses of beauty, where the focus is less on what beauty is or what it means, and more on how it comes to be.